Low intrathecal antibody production despite high seroprevalence of Epstein-Barr virus in multiple sclerosis: a review of the literature - Ruprecht, Klemens; Wildemann, Brigitte; Jarius, Sven (Journal of neurology, 2018)
Background: Patients with multiple sclerosis (MS) frequently have an intrathecal production of antibodies to different common viruses, which can be detected by elevated antiviral antibody indices (AIs). There is a strong and consistent association of MS and Epstein-Barr virus (EBV) infection.Objective:To systematically compare the frequencies of intrathecal antibody production to EBV, measles virus, rubella virus, varicella zoster virus (VZV) and herpes simplex virus (HSV) in patients with MS.Methods: Review of the English and German literature on the frequencies of intrathecal immunoglobulin (Ig)G antibody production, as defined by an elevated AI, to EBV, measles virus, rubella virus, VZV and HSV in adult and pediatric patients with MS. Results: In nine original studies identified, the frequencies of an intrathecal production of antibodies to Epstein-Barr nuclear antigen-1 (33/340, 9.7%), EBV viral capsid antigen (12/279, 4.3%) and antigens from EBV-infected cell lines (14/90, 15.6%) in adult patients with MS were clearly lower (p ≤ 0.03 for all pairwise comparisons) than the frequencies of an intrathecal production of antibodies to measles virus (612/922, 66.4%), rubella virus (521/922, 56.5%), VZV (470/922, 51%; data from 17 original studies) and HSV (78/291, 26.8%; data from 6 original studies). Though based on a lower number of original studies and patients, findings in children with MS were essentially similar. As in adults and children with MS the seroprevalence of EBV is higher than the seroprevalences of the other investigated viruses, the lower frequency of elevated EBV AIs became even more pronounced after correction of the frequencies of elevated antiviral AIs for the seroprevalences of the respective viruses.Conclusions: Given the very high seroprevalence of EBV in MS, the frequency of intrathecally produced antibodies to EBV in patients with MS is paradoxically low compared to that of other common viruses. These findings are compatible with the recently proposed hypothesis that in individuals going on to develop MS antiviral antibody-producing cells may invade the brain predominantly at the time of and triggered by acute primary EBV infection, before anti-EBV IgG producing cells have yet occurred.
Gesehen am 23.05.2018
First Online: 02 November 2017